Mesenchymal stem cell treatment restores liver macrophages homeostasis to alleviate mouse acute liver injury revealed by single-cell analysis. (May 2022) - Zhou, Jiahang; Feng, Xudong; Zhu, Jiaqi; Feng, Bing; Yao, Qigu; Pan, Qiaoling; Yu, Jiong; Yang, Jinfeng; Li, Lanjuan; Cao, Hongcui
Abstract: Acute liver injury (ALI) is characterized by massive hepatocyte necrosis and subsequent recruitment of myeloid cells to liver. Mesenchymal stem cells (MSCs) have therapeutic potential for ALI through their immunoregulation on macrophages, but the mechanism is not completely clear due to the heterogeneity and controversy of liver macrophages. Here, we detected the survival rate, biochemical indexes, histopathology, and inflammatory chemokine levels to assess the efficacy of MSC treatment on CCl4 -induced ALI of C57BL/6 mice. Furthermore, flow cytometry and single-cell RNA sequencing (scRNA-Seq) were used to precisely distinguish macrophage populations and reveal the immunoregulation of MSCs. MSC treatment could effectively alleviate ALI and mitigate the recruitment of mononuclear phagocytes. Flow cytometry and scRNA-Seq analyses collectively indicated that there were monocytes with high Ly6C expression and heterogeneous monocyte-derived macrophages (MoMF) with low Ly6C expression in liver. Ly6C hi pro-inflammatory monocytes and Ly6C lo MoMF with powerful phagocytosis dominated during the acute injury period. MSC treatment promoted the transition from Ly6C hi to Ly6C lo population, inhibit the proinflammatory function of monocytes and promote the lysosomal function of MoMF. Furthermore, MSCs attenuated the recruitment of neutrophils by reducing the expression of CXCL2 of MoMF. MoMF with high expression of arginase 1 appeared during the recovery period, and MSCs could increase their expression of arginase 1, which may promote liver repair. To sum up, we demonstrated the characteristics of distinct MoMF during different periods of ALI and revealed their functional changes after MSC treatment, providing immunotherapeutic targets for MSC treatment of ALI. Graphical Abstract: ga1